Evaluation of fibrinolysis in menopausal women suffering from lower limb deep vein thrombosis - Stefańczyk, Ludomir; Owczarek, Danuta; Stachowiak, Grzegorz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
We have analyzed fibrinolytic system status in menopausal subjects with lower limb deep vein thrombosis (LLDVT), being users or non-users of hormone replacement therapy at the same time. The women were divided into three groups: 1) group H (LLDVT + HRT); 2) group Z (LLDVT, no HRT); 3) group K (controls – HRT, without LLDVT). Plasminogen activity, concentrations of D-dimer, PAI-1, t-PA and PAP complexes were measured in blood serum. DVT was diagnosed in ultrasound examinations (US-CD). Results: 1) enhanced D-dimer levels in group H; 2) high concentrations of PAI-1 and PAP in all groups. Conclusions: 1) Menopausal period is characterized by impaired systemic fibrinolysis. 2) LLDVT in HRT users is detected earlier than in women without hormonal treatment.